Environmental governance and policy in Kazakhstan - Lyazzat Nugumanova; Miriam Frey (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
We provide a comprehensive overview of the current state of environmental governance and policy in Kazakhstan as the country is assumed to have a leading role in Central Asia in terms of green growth and sustainable development. The overview of the environmental and institutional framework in the country reveals that the significant steps towards an improvement of environmental governance have been undertaken.
Keywords: Q50; Q58; Q59; 330; environmental governance; environmental policy; institutions; Kazakhstan